HEALTH-FORMATION OF COMPETENCE UNIVERSITY PROFESSORS MEANS INFORMATION AND COMMUNICATION TECHNOLOGIES - Olena Sokolyuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article presents the theoretical foundations of the process of formation of health-preserving competences among university teachers by means of information and communication technologies as a prerequisite for quality training of future specialists. The concepts of «competence», «health-preserving competence» at the level of professional development of university teachers have been analyzed. Current approaches, activities in the formation of health-preserving competences of university teachers and efficiency of their use in education have been studied in the article. Special attention has been put into the formation of health-preserving competence among university teachers by means of information and communication technologies.